(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2025)
Functional redundancy – the extent to which multiple species within an ecological community perform the same functional roles, providing insurance against the loss of ecosystem functions when species are extirpated – is a foundational concept in biodiversity-ecosystem functioning research and conservation biology. Yet its empirical quantification across ecosystem types, its relationship to biodiversity, and its actual buffering effect on ecosystem function stability under species loss scenarios remain incompletely characterised at global scales. This study conducted the most comprehensive cross-ecosystem functional redundancy analysis yet assembled, quantifying functional redundancy using three complementary metrics – functional overlap, community-weighted mean trait variance, and functional extinction debt – across 247 ecological communities spanning grasslands, forests, coral reefs, kelp forests, freshwater streams, and wetlands in 38 countries. Functional redundancy was significantly positively correlated with species richness (Spearman rs = 0.74, p < 0.001) but with substantial explained variance remaining (R2 = 0.54), indicating that richness alone is an incomplete predictor of redundancy. Ecosystem type was the strongest single predictor of redundancy: coral reefs showed the highest redundancy (mean functional overlap = 0.84 +- 0.08), while freshwater streams showed the lowest (0.31 +- 0.11). Simulation of species loss scenarios – removing species by order of threat status (most-to-least threatened first) – showed that threatened-species-prioritised extinction sequences eroded ecosystem function stability 2.8 times faster than random extinction sequences, because threatened species are disproportionately functionally unique. Communities with higher baseline functional redundancy showed 47.4% smaller functional loss under simulated 25% species richness reduction (p < 0.001). These results confirm that functional redundancy is a critical mediator of ecosystem resilience and argue for its incorporation into biodiversity monitoring and conservation prioritisation frameworks.